(untitled) (American Journal of Research in Humanities and Social Sciences, 2022)
Social knowledge occupies a special place in the system of sciences and has specifics due to the circumstances of its formation, the specifics of the object of research and the properties of the cognizing subject. In this article highlights of dependence of social knowledge and innovation.